Prediksi Penurunan Konsolidasi Menggunakan Preloading dan Prefabricated Vertical Drain dengan Software Metode Elemen Hingga - Tika Ermita Wulandari (Universitas Medan Area, 2021)
Consolidation is the process of removing water from the pores of the soil which causes changes in the volume of the soil which results in damage to the construction above it. This is more fatal if the decline that occurs is local. Nowadays the use of vertical drains is increasingly in demand, especially with the Prefabricated Vertical Drain (PVD) system which can reduce the time of the soil consolidation process significantly from several years to a matter of months and with technological advances, software is created that can make it easier to calculate construction work with computer programs, one of which is the only finite element method software (Plaxis) to calculate the consolidation settlement process. This study aims to analyze using Finite Element Method software with the help of 2D and 3D plaxis programs to get the consolidation settlement size. The results of 2D and 3D modeling will be compared so that the results that are closest to the field conditions are obtained. From the results of the analysis, it can be concluded that the magnitude of the decrease in Plaxis 3D is closer to the settlement plate data S29 with a decrease of 6.956m or a difference of -0.234m, while the magnitude of the decrease in Plaxis 2D is 7.491 with a difference of decrease of 0.301m.